2022
DOI: 10.1253/circj.cj-21-0958
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of Smoking-Related Aryl-Hydrocarbon Receptor Repressor (<i>AHRR</i>) Hypomethylation in Japanese Adults

Abstract: at many loci across the genome, 3 and that smoking-related changes in gene expression are epigenetically regulated. 4 Among EWAS-identified loci, the aryl-hydrocarbon receptor repressor (AHRR) gene has been noted as a promising candidate gene, with smoking-associated hypomethylation of AHRR CpG sites (e.g., cg05575921) detectable in DNA from peripheral lymphocytes and pulmonary macrophages. 5,6 AHRR encodes a transcription factor that can repress the aryl-hydrocarbon receptor pathway, which regulates the cytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…It has been previously demonstrated that a bisul te converted DNA ddPCR assay can accurately determine the CpG methylation status of cg05575921 within AHRR (3,4,13). Furthermore, strong concordance between BIS ddPCR and Illumina Epic array measures of cg05575921 have been reported (4,13).…”
Section: Resultsmentioning
confidence: 97%
“…It has been previously demonstrated that a bisul te converted DNA ddPCR assay can accurately determine the CpG methylation status of cg05575921 within AHRR (3,4,13). Furthermore, strong concordance between BIS ddPCR and Illumina Epic array measures of cg05575921 have been reported (4,13).…”
Section: Resultsmentioning
confidence: 97%
“…4 In this issue of the Journal, Takeuchi et al add more detailed evidence. 5 Through an EWAS in a Japanese population, they not only validated the association between AHRR cg05575921 demethylation and smoking status, but also showed that smoking-related AHRR cg05575921 hypomethylation remains for a long period of time, 20 years or more, even after smoking cessation. 5 They also reveal that AHRR cg05575921 hypomethylation appears to become evident from a relatively early stage of smoking (i.e., <10 years) among current smokers.…”
Section: Article P 986mentioning
confidence: 87%
“…5 Through an EWAS in a Japanese population, they not only validated the association between AHRR cg05575921 demethylation and smoking status, but also showed that smoking-related AHRR cg05575921 hypomethylation remains for a long period of time, 20 years or more, even after smoking cessation. 5 They also reveal that AHRR cg05575921 hypomethylation appears to become evident from a relatively early stage of smoking (i.e., <10 years) among current smokers. These results suggest that AHRR cg05575921 hypomethylation is a quantifiable marker of smoking habits, including early stage or cessation stage of smoking.…”
Section: Article P 986mentioning
confidence: 87%
“…Here, we only observed a trend between AHRR methylation at cg21161138 and AHRR mRNA expression in epithelial cells, potentially because of the relatively lower power due to drop-outs. Nevertheless, previous studies have shown that smoking-related hypomethylation of AHRR is correlated with AHRR mRNA expression in blood, lung tissue and lung-derived macrophages [ 13 , 31 , 32 ], suggesting that the gene expression of AHRR is regulated by DNA methylation. Additionally, we observed a negative correlation between the expression of AHRR and AHR , which indicates that AHRR indeed regulates the expression of AHR in human airway epithelium.…”
Section: Discussionmentioning
confidence: 99%